Maximal oxygen consumption, respiratory volume and some related factors in fire-fighting personnel - Touraj Khazraee; Mohammad Fararouei; Hadi Daneshmandi; Farzane Mobasheri; Zahra Zamanian (International Journal of Preventive Medicine, 2017)
Background: Firefighters for difficult activities and rescue of damaged people must be in appropriate physical ability. Maximal oxygen capacity is an indicator for diagnosis of physical ability of workers. This study aimed to assess the cardiorespiratory system and its related factors in firefighters. Methods: This study was conducted on 110 firefighters from various stations. An self-administered questionnaire (respiratory disorders questionnaire, Tuxworth-Shahnavaz step test, and pulmonary function test) was used to collection of required data. Average of humidity and temperature was 52% and 17°C, respectively. Background average noise levels were between 55 and 65 dB. Data were analyzed using SPSS software (version 19). Results: The mean age of the study participants was 32 ± 6.2 years. The means of forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), and FEV1/FVC were 92% ±9.4%, 87% ±9.2%, and 80% ±6.1%, respectively. The participants' mean VO2-max was 2.79 ± 0.29 L/min or 37.34 ± 4.27 ml/kg body weight per minute. The results revealed that weight has a direct association with vital capacity (VC), FVC, and peak expiratory flow. In addition, height was directly associated with VC, FVC, and VO2-max (P < 0.05). However, there was an inverse and significant association between height and FEV1/FVC (r = −0.23,P< 0.05). Height, weight, body mass index, and waist circumference were directly associated with VO2-max. Conclusions: The findings of this study showed that the amount of maximum oxygen consumption is close with the proposed range of this parameter among firefighters in other studies. Furthermore, the results of the study revealed that individuals had normal amounts of lung volume index. This issue can be attributed to the appropriate usage of respiratory masks.